A series of articles celebrates historical Finnish women who wrote music - Susanna Välimäki; Nuppu Koivisto (Music Finland, 2022)
The article presents an article series about historical women composers in Finland by Susanna Välimäki and Nuppu Koivisto.The article series derives from their book project titled Sävelten tyttäret: Säveltävät naiset Suomen historiassa 1700-luvun lopulta 1900-luvun alkuun [Daughters of music: Finnish Women Composers, from the late 18th to the early 20th centuries],which  discusses the lives and music of historical women composers in Finland. The article presents briefly some of the composers and interesting projects on women, music and equality.